Bibliographical note: D. Holton – G. Horrocks – M. Jannsen –T. Lendari – I. Manolessou – N. Toufexis, The Cambridge Grammar of Medieval and Early Modern Greek. Vol. 1. General Introduction and Phonology [σελ. clxx, 1-238]. – Vol. 2. Nominal Morphology [σελ. xxii, 239-1264]. – Vol. 3. Verb Morphology [σελ. xxii, 1265-1858]. – Vol. 4. Syntax [σελ. xvi, 1859-2094], Cambridge 2019 - ΛΑΜΠΑΚΗΣ, Στυλιανός (Byzantina Symmeikta, 2020)
Bibliographical note:D. Holton – G. Horrocks – M. Jannsen –T. Lendari – I. Manolessou – N. Toufexis, The Cambridge Grammar of Medieval and Early Modern Greek. Vol. 1. General Introduction and Phonology [σελ. clxx, 1-238]. – Vol. 2. Nominal Morphology [σελ. xxii, 239-1264]. – Vol. 3. Verb Morphology [σελ. xxii, 1265-1858]. – Vol. 4. Syntax [σελ. xvi, 1859-2094], Cambridge 2019